2003
DOI: 10.1590/s0103-90162003000400007
|View full text |Cite
|
Sign up to set email alerts
|

Rhipsalis grandiflora Haw. (Cactaceae) propagation by setem cuttings

Abstract: The genus Rhipsalis is being cultivated as a potted plant since the view of the pendant branches with coloured flowers and fruit is very appreciated. Considering that there is no information about the production of rooted propagules of these species, the goal of this work was to evaluate the development of stem cuttings, stimulated by the application of plant growth regulators. The indolebutyric acid (IBA) was tested at 0; 4.07; 5.81, and 11.63 mmol L-1 and the naphthaleneacetic acid (NAA) at 0; 4.53; 6.47, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Seran and Umadevi (2011) reported that stem cuttings of Citruslimon L. treated with IAA were able to produce a large number of new leaves because they had developed a vigorous rooting system. Stancato et al (2003) showed that roots enabled cuttings to absorb more nutrients and produce more leaves. Cuttings with more new leaves and more shoots showed higher survivorship rates when grown in natural conditions (Pessarakli, 2002).…”
Section: Effects Of Auxin Types and Concentrations On Survival And Romentioning
confidence: 99%
“…Seran and Umadevi (2011) reported that stem cuttings of Citruslimon L. treated with IAA were able to produce a large number of new leaves because they had developed a vigorous rooting system. Stancato et al (2003) showed that roots enabled cuttings to absorb more nutrients and produce more leaves. Cuttings with more new leaves and more shoots showed higher survivorship rates when grown in natural conditions (Pessarakli, 2002).…”
Section: Effects Of Auxin Types and Concentrations On Survival And Romentioning
confidence: 99%
“…The minimum (2.33) number of leaves per cutting were recorded in control. Increase in leaf number may be due to vigorous rooting induced by the growth regulator enabling the cuttings to absorb more nutrients and thereby producing more leaves as reported by Stancato et al, (2003).…”
Section: Resultsmentioning
confidence: 89%
“…The increase in auxin concentration positively influenced shoot formation in J. parkeri cuttings and treatment with IAA at 2000 ppm resulted in the production of the maximum number of leaves and greatest shoot length. According to Stancato et al [24], the escalation in leaf number could be due to the presence of a vigorous rooting system induced by auxin treatment, enabling the cuttings to absorb additional nutrients, thus resulting in the production of more leaves. Reddy et al [25] reported maximum cumulated shoot length (5.73 cm) in Pelargonium graveolens cuttings treated with IAA at 2000 ppm concentration.…”
Section: Discussionmentioning
confidence: 99%